1992
DOI: 10.1288/00005537-199209000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus identified by nucleic acid hybridization in concomitant nasal and genital papillomas

Abstract: Presence of human papillomavirus (HPV) as the etiologic agent in nearly all upper respiratory tract recurrent papillomas is well-established. The technique of nucleic acid hybridization now allows specific typing of HPV with a high degree of accuracy. This article reports a series of nine consecutive patients treated for nasal papillomas over the past 9 years. Eight of these patients had a personal history of genital papillomas (seven patients) or exposure (one patient). With the use of in situ hybridization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…However, the viral aetiology could be a possible explanation for multicentric disease in some patients, resulting in multiple recurrences in spite of a radical resection. 17 As only low-risk HPV types were detected in our series and no correlation was found to malignancy and recurrence of disease, screening for HPV seems not to be useful as a prognostic parameter.…”
contrasting
confidence: 59%
“…However, the viral aetiology could be a possible explanation for multicentric disease in some patients, resulting in multiple recurrences in spite of a radical resection. 17 As only low-risk HPV types were detected in our series and no correlation was found to malignancy and recurrence of disease, screening for HPV seems not to be useful as a prognostic parameter.…”
contrasting
confidence: 59%
“…Among them, all of seven recurrent cases contained HPV DNA. Klemi et al [7] also reported that all four cases of recurrent sinonasal papillomas yielded HPV DNA types 11/16, and Fu et al [12] reported all three recurrent fungiform nasal papillomas studied had HPV DNA types 6/11. Conversely, HPV was not detected in normal nasal mucosa [13].…”
Section: Detection Of Hpv Dna By Southern Blot Hybridisationmentioning
confidence: 95%
“…Among them, four (SO.OO/) of the five recurrent cases (cases 1-5) were HPV DNA-positive whereas only one (14.3%) of seven non-recurrent cases (cases [6][7][8][9][10][11][12] was HPV DNA-positive. The detection rate of HPV DNA in recurrent cases analysed by Fisher's exact probability test was significantly higher than that in non-recurrent cases (p = 0.045).…”
Section: Detection Of Hpv Dna By Pcrmentioning
confidence: 96%
See 1 more Smart Citation
“…Focal epithelial hyperplasia is often associated with HPV-13 [50] and HPV-32 [51], which are not found in other lesions. Exophytic nasal papillomas also usually contain HPV-6 or HPV-11 [52][53][54][55][56][57], although HPV-57b has been identified in both exophytic and inverted papillomas of the nasal cavity [58]. Most exophytic papillomas are HPV positive (70 to 75%), while the reported frequency of HPV DNA detection in inverting papillomas ranges from 0% to 89%.…”
Section: Hpv and Respiratory Papulomatosismentioning
confidence: 99%